The Relationship Between Teachers' Pedagogical Competence And Fifth-Grade Students' Learning Motivation - Fela Fela; Nikolaus Passasung; Kasmawati Kasmawati (Journal of Education and Learning Sciences, 2025)
This study was motivated by the important role of teachers' pedagogical competence in supporting students' learning motivation at the elementary-school level. The study aimed to examine the relationship between teachers' pedagogical competence and the learning motivation of fifth-grade students at SD Negeri 12 Konda. A quantitative correlational design was employed, involving all 29 fifth-grade students selected through total population sampling. Data were collected using two 20-item Likert-scale questionnaires measuring teachers' pedagogical competence (X) and students' learning motivation (Y). Both instruments demonstrated satisfactory validity, with calculated r values ranging from 0.558 to 0.846, exceeding the critical r value of 0.374, and high reliability, with Cronbach's alpha coefficients of 0.956 for the pedagogical competence instrument and 0.955 for the learning motivation instrument. The data were analyzed using the Shapiro–Wilk normality test, linearity test, and Pearson product-moment correlation in IBM SPSS Statistics. The results showed that both variables were normally distributed, with significance values of 0.087 for teachers' pedagogical competence and 0.126 for students' learning motivation, both exceeding 0.05. The Pearson correlation analysis revealed a very strong, positive, and statistically significant relationship between teachers' pedagogical competence and students' learning motivation (r = 0.998; p < 0.001). The coefficient of determination (R² = 0.996) indicated that 99.6% of the variance in students' learning motivation was statistically associated with variation in teachers' pedagogical competence, while the remaining 0.4% was related to other factors outside the scope of the study. These findings indicate that higher levels of teachers' pedagogical competence are strongly associated with higher levels of learning motivation among fifth-grade students.